Child care service and economic development in Kota Kinabalu, Sabah - Jenifer Nogo Matheus; Janice L. H. Nga; Wijaya Kamal Ramlan; Jonghyun Park (Global and Regional Research Institutes, Hosei University (GRRI), 2018)
Child care is an institutions where children are prepare to enter a social and educational based environment whereas Child care centre means any premises at which four or more children under the age of four years from more than one household are received to be looked after for reward. It is very important for child care businesses to meet the needs of parents in order to attract and retain their customer. In that, this study discuss on the contribution of child care to economic development based in Kota Kinabalu, Sabah only. The contributions have been looked into two terms which are the child care yearly fees and on the employment opportunities to the child care teacher and staff .Data was collected using an interview session with the child care teacher and staff were conducted to collect the data on the total employee, total child registered and also fees been charge in their child care. There are 76 child care centre that participate in this study. While this study is focusing in Kota Kinabalu, its findings can be useful for future research expansion in other region.